Effectiveness of Carica Papaya Leaves and Tinospora Crispa Stems Against Paracoccus Marginatus in Eucalyptus Nursery - Irfani, Ewi; Aditia, Windy Sukma; Mardhiansyah, M.; Pebriandi, Pebriandi (Jurnal Biologi Tropis, 2025)
One of the pests that attacks Eucalyptus pellita is Paracoccus marginatus. Currently, chemical pesticides are used to control these pests, which can harm health and the environment. As a result, we need a more environmentally friendly alternative biopesticides that comes from a combination of Carica papaya leaf and Tinospora crispa stem extracts. The aim of this research was to determine the effect of Carica papaya leaf and Tinospora crispa stem extracts on Paracoccus marginatus pests in eucalyptus nurseries and to determine the best concentration for controlling Paracoccus marginatus pestsThe experiment used a completely randomized design (CRD) with 4 treatments and 4 replications. The treatments consisted of different concentrations of Carica papaya leaf and Tinospora crispa stem extracts (20, 40, 60, and 80 g/l). This was followed by a DNMRT test at 5% confidence level. The results showed that the combination of Carica papaya leaf and Tinospora crispa stem extracts significantly affected Paracoccus marginatus mortality. The best concentration of the extract mixture was 80 g/l, which resulted in the fastest mortality rate, with an LT50 of 26.41 hours and 100% total mortality.